DOP24 Intestinal acidification sensed by pH-sensing receptor GPR4 contributes to fibrogenesis. (25th January 2019) - Weder, B; Van Haaften, W T; Baebler, K; Rogler, G; Dijkstra, G; Imenez Silva, P H; Wang, Y; De Vallière, C; Wagner, C; Frey-Wagner, I; Seuwen, K; Ruiz, P; et al.
Abstract: Background: During active inflammation, intraluminal intestinal pH is decreased in patients with inflammatory bowel disease (IBD). Acidic pH may play a role in IBD pathophysiology. pH-sensing G-protein-coupled receptor (GPR) 4 is regulated by key inflammatory cytokines. Patients suffering from IBD express increased mucosal levels of GPR4 compared with non-IBD controls. pH-sensing may be relevant for progression of fibrosis, as extra-cellular acidification leads to fibroblast activation and extracellular matrix remodelling. We aimed to determine GPR4 expression in fibrotic lesions in the intestine of Crohn's disease (CD) patients, and the effect of Gpr4 deficiency in fibrogenesis. Methods: Human fibrotic and non-fibrotic terminal ileum was obtained from CD patients undergoing ileocaecal resection due to stenosis. Gene expression of fibrosis markers and pH-sensing receptors was analysed. The in vivo murine model of DSS-induced chronic colitis and the heterotopic transplantation model of intestinal fibrosis was used. Collagen layer thickness and hydroxyproline content were determined. Primary human fibroblast cultures were obtained from surgical specimens taken from healthy areas of the mucosa of a patient undergoing surgery for colorectal carcinoma. Fibroblasts were exposed to pH 6.4, 7.4, and 7.8 for 3 and 24 h, respectively, and additionally stimulated with recombinant TGF. Results: Increased expression of fibrosis markers was accompanied by an increase of GPR4 (3.07 ± 1.03 vs. 0.80 ± 0.12, p = 0.035) in fibrosis-affected human terminal ileum, compared with the non-fibrotic resection margin. Positive correlation between GPR4 expression and pro-fibrotic cytokines (TGF and CTGF) or pro-collagens was observed. Gpr4−/− mice from both the DSS-induced chronic colitis model and the heterotopic transplantation animal model for intestinal fibrosis showed a significant decrease in mRNA expression of fibrosis markers as well as a decrease in collagen layer thickness and hydroxyproline compared with wild-type mice. In vitro, GPR4 expression was increased at low pH (6.4) compared with normal (7.4) and high pH (7.8). Expression of pro-fibrotic TGF and collagen was increased at low pH. Last but not at least, exposure to low pH triggered nuclear translocation of p-SMAD3, pointing to the activation of the TGF signalling pathway upon low pH stimulation. Conclusions: GPR4 expression correlates with the expression of pro-fibrotic genes and increased levels of collagen deposition. Gpr4 deficiency is associated with a decrease in fibrosis formation. Targeting GPR4 may be a potential new treatment option for IBD-associated fibrosis.